NEEDS ANALYSIS OF ETHNOSCIENCE-BASED DIGITAL TEACHING MATERIALS FOR SCIENCE AND SOCIAL STUDIES (IPAS) ON ECOSYSTEM TOPICS FOR GRADE V ELEMENTARY SCHOOL - I Kadek Yudi Suastawan; Kadek Hengki Primayana; I Made Ari Winangun (LEARNING : Jurnal Inovasi Penelitian Pendidikan dan Pembelajaran, 2026)
ABSTRACT The continued reliance on printed teaching materials in elementary science (IPAS) ecosystem learning has created a gap between the presentation of scientific concepts and students' authentic learning experiences. This challenge becomes more evident when instructional materials fail to accommodate students' diverse learning needs while overlooking the potential of local wisdom as a meaningful contextual learning resource. This study aimed to identify the instructional needs for developing ethnoscience-based digital teaching materials for fifth-grade elementary students as a foundation for designing more adaptive learning resources. A qualitative descriptive approach was employed using a needs analysis framework through classroom observations, in-depth interviews with teachers, and document analysis of instructional planning conducted at SD Negeri 3 Penglatan and SD Negeri 1 Penglatan. The findings revealed that the predominance of static printed materials contributed to less engaging learning experiences and was insufficient to address the heterogeneity of students' academic abilities. The analysis further identified the need for interactive, flexible, and contextual digital teaching materials that support differentiated learning by integrating the Subak irrigation system as a representation of local ethnoscience. These findings provide a strong empirical basis for developing ethnoscience-based digital teaching materials and offer a conceptual foundation for designing elementary IPAS learning that is more adaptive, meaningful, and responsive to students' characteristics and local cultural contexts. ABSTRAK Kecenderungan penggunaan bahan ajar cetak pada pembelajaran IPAS materi ekosistem di sekolah dasar masih menyisakan kesenjangan antara penyajian konsep ilmiah dengan pengalaman belajar yang dekat dengan kehidupan peserta didik. Kondisi tersebut semakin terasa ketika materi belum mengakomodasi keberagaman kemampuan belajar siswa maupun potensi kearifan lokal sebagai sumber belajar yang kontekstual. Penelitian ini bertujuan mengidentifikasi kebutuhan pengembangan bahan ajar digital berbasis etnosains bagi siswa kelas V sekolah dasar sebagai dasar penyusunan desain pembelajaran yang lebih adaptif. Penelitian menggunakan pendekatan deskriptif kualitatif melalui needs analysis dengan tahapan observasi pembelajaran, wawancara mendalam bersama guru, serta analisis dokumen perangkat pembelajaran yang dilaksanakan di SD Negeri 3 Penglatan dan SD Negeri 1 Penglatan. Hasil penelitian menunjukkan bahwa dominasi media cetak statis menyebabkan pembelajaran kurang menarik dan belum mampu mengakomodasi heterogenitas kemampuan akademik siswa. Analisis juga mengungkap kebutuhan terhadap bahan ajar digital yang mendukung pembelajaran berdiferensiasi melalui penyajian konten yang interaktif, fleksibel, dan kontekstual dengan mengintegrasikan sistem Subak sebagai representasi etnosains lokal. Temuan tersebut menegaskan bahwa pengembangan bahan ajar digital berbasis etnosains memiliki landasan kebutuhan yang kuat sebagai acuan konseptual dalam merancang pembelajaran IPAS yang lebih adaptif, bermakna, dan relevan dengan karakteristik peserta didik serta lingkungan budayanya.